#TITLE_ALTERNATIVE# - KATRI LASRINDY (NIM: 12909014); pembimbing: Dr. Eng. Totok Suprijo ; Dr. Fitri Riandini, ANDARU
A three dimensional model, namely ECOMSED, has been employed in Tanara Waters-Banten to simulate sediment transport for 22 days from April 7th to 29th 2012. The simulation has been done into two steps. The first step is to simulate the hydrodynamics of the large model that covers part of the Java Sea. The second is the small model which is the coupled model of hydrodynamics and sediment distribution that covers Tanara Waters. The tidal components from TMD (Tidal Model Driver) were used on the open boundary. There are three rivers that flow on Tanara, which are Ciujung River, Cidurian River, and Cidurian Creeks. The discharges of the three rivers are 50 m3/s, 30 m3/s, and 20 m3/s, respectively.The sediment type is cohesive (mud) and the concentration on source is 500 mg/l for each river. Horizontal profiles of current show backward and forward pattern along the coast, specifically eastward at flood tide and westward at ebb tide. The verification result in this study shows acceptable RMSE, 0.08 m for the large model and 0.07 m for the small model for the tidal elevation, while the flow of the small model velocity u is 0.009 m/s and v is 0,012 m/s. Sediment moved eastward at flood tide and carried to the west at ebb tide. The verification towards suspended load measurement resulted RMSE value of 6,4 mg/l. The horizontal profiles of sediment distribution show that sediment moved along the coast.